El Derecho Internacional de los Derechos Humanos en el Derecho Positivo y la jurisprudencia constitucional costarricense - Solís, Alex (2014)
According to the Constitution and Constitutional Court jurispru- dence, it becomes clear that Human Rights International Law has a chief place within the legal system. This study explains that such law complements the human rights set forth in the Constitution, while it serves as criteria for interpretation. But most importantly, it emphasizes the fact that Human Rights International Law does not have a value similar to that of the Constitution, but a higher one, as it provides greater rights and guarantees than those under our own Constitution.